Cell Recoverability and Metabolism of Colwellia Psychrerythraea at a Range of Sub-Zero Temperatures, 2021 ... - Firth, Evan; Junge, Karen (NSF Arctic Data Center, 2024)
Liquid water is essential to life as we know it, yet most planets and moons in our solar system have surface temperatures well below the freezing point of pure water. As part of an effort to identify potential biosignatures and biosignature targets for upcoming space-exploration life detection missions, arctic strain Colwellia psychrerythraea 34H was incubated at -5, -36, and -196 degrees Celsius (°C) over the course of a week, with time points as short as 0.5 hours (h). Samples were examined for cell abundance, recoverability, and metabolic activity over the course of the incubation period to accompany 13C6-Leucine incorporation proteomic data. This is the compiled raw data that accompanies the proteomic data (-5°C only; The mass spectrometry proteomics data are publicly available on the ProteomeXchange Consortium via the PRIDE partner repository with the dataset identifier PXD059470. Additionally, an interactive proteomic data analysis from all experiments is available on the Limelight Server ...